ANALISIS PEMAHAMAN KONSEP DALAM MENYELESAIKAN OPERASI HITUNG PERKALIAN PADA SISWA KELAS III SD IT SAMAWA CENDEKIA - Viya Nuruli Rifanti; Nasaruddin Nasaruddin; Awal Nur Kholifatur Rosyidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2021)
Abstract: Mathematics is one of the compulsory subjects in elementary school. Students are required to have four basic math competencies, one of them is multiplication. This research aims to identify the conceptual understanding of students in understanding the multiplication arithmetic operations and the difficulties experienced by students in completing it as well as the factors that influence the difficulty. The type of this research is qualitative research using descriptive methods. The research was conducted at SD IT Samawa Cendekia in October 2020 and the subjects are 30 students from the third grade of Ad-Dhailami. The instruments are test, interview and documentation. The data analysis technique used is the interactive data analysis model Miles and Huberman which consists of data reduction, data presentation and conclusion. The results showed that there were 20 students who did not understand the concept of multiplication and 10 students understood. The difficulties experienced by students in completing multiplication arithmetic operations include: Not being able to distinguish between the multiplier and the numbers being multiplied; Difficulty understanding sentences in story problems; Difficulty to solve math problems related to everyday problems; forget the basic multiplication ; can not change the form of multiplication to the form of repeated addition; Cannot determine the sentence that is known and the sentence asked in the story problem; Cannot solve multiplication calculation operation problems independently. Factors that influence that the difficulties experienced happened by students are not understanding the concept of multiplication, using the rote method in learning multiplication arithmetic operations.